Development of a Linux Kernel Driver for the SBNI Network Interface Using Remote Real-Time Processing Units - Rebus, Ilya; Frantsuzova, Galina; Kolker, Alexey (2025 IEEE 26th International Conference of Young Professionals in Electron Devices and Materials (EDM), 2025)
This article covers the subject of developing a Linux kernel driver for the existing SBNI network interface for twisted-pair leased lines, which is used to provide long-range data transmission in a dangerous environment of underground mining facilities. Siberian Board Network Interface (SBNI) was developed at the end of 90 -s of the XX century by a company named "Granch". It is used in an automated monitoring and positioning system"SBGPS", which uses industrial controllers, base stations and other equipment provide communication, environmental readings, personnel and vehicle geolocation for the mining industry. This article contains an explanation of the Linux kernel driver development process, which includes implementation of real-time processing units that are present in PRU-ICSS system (Programmable Real-Time Units and Industrial Communication Subsystem). It is a part of the Texas Instruments Sitara AM3358 processor, which is used in base stations and industrial controllers of the SBGPS system. This article also contains the results of the testing phase of the developed solution.